Economic feasibility of methoprene applied as a surface treatment and as an aerosol alone and in combination with two other insecticides - Fontenot, Emily A.; Arthur, Frank H.; Nechols, James R.; Langemeier, Michael R. (My University, 2013)
Economic evaluations of integrated pest management strategies are becoming increasingly important as restrictions on conventional insecticides continue to become more stringent and chemical control costs rise. Aerosol treatments with insect growth regulators alone and in combination with conventional contact insecticides may be a feasible alternative to expensive and highly toxic fumigants such as methyl bromide for control of the Indianmeal moth (Plodia interpunctella (Hübner)). Average calculated mortality of Indianmeal moth eggs exposed to surface applied methoprene, aerosol methoprene alone and in combination with esfenvalerate and synergized Pyrethrins is 55.0, 69.0, and 94.6%, respectively. Temperature effects on development time makes frequency and timing of insecticide applications very important as evidenced by simulations of population levels in response to a variety of treatment dates by diet, and become critical in situations where survival of Indianmeal moth is high. Using a measurement of risk that is equal to deviations below a target mortality goal (99%), we are able to optimize cost and frequency of application using simulated mortality data for each of the treatment strategies. Optimal timing of each insecticide treatment depends heavily on the rate of development by diet. This type of analysis helps pest control operators and managers by showing consequences of treatment scenarios in time and cost.
Keywords: Methoprene; Esfenvalerate; Plodia interpunctella Hübner; Economic analysis